2013
DOI: 10.2967/jnumed.112.111955
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition Protocols and Correction Methods for Estimation of the Heart-to-Mediastinum Ratio in 123I-Metaiodobenzylguanidine Cardiac Sympathetic Imaging

Abstract: Septal penetration of high-energy photons affects quantitative results in imaging of 123 I-labeled tracers. We investigated acquisition protocols (collimator choice and energy window setting) and correction methods for estimating the heart-to-mediastinum (H/M) ratio in cardiac 123 I-metaiodobenzylguanidine (MIBG) imaging. Methods: Four hours after 123 I-MIBG injection, 40 patients successively underwent planar anterior chest imaging with the medium-energy (ME) (ME method) and low-energy high-resolution (LEHR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…130,131 Although most clinical literature is based on use of a LEHR, in fact the reported HMRs are severely underestimated in relation to the true value. 132 Several methods have been explored attempting to overcome this problem when an LEHR is used, including mathematical deconvolution of septal penetration (DSP), 130 image acquisition using 123 I-dual window acquisition (IDW), 133 decreasing the 159-kEV energy window to 15%. 132 Although it has been suggested that a medium-energy collimator may be preferred, 129 use of a calibration phantom to derive a conversion coefficient for each camera-collimation system may be a better approach.…”
Section: Imaging Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…130,131 Although most clinical literature is based on use of a LEHR, in fact the reported HMRs are severely underestimated in relation to the true value. 132 Several methods have been explored attempting to overcome this problem when an LEHR is used, including mathematical deconvolution of septal penetration (DSP), 130 image acquisition using 123 I-dual window acquisition (IDW), 133 decreasing the 159-kEV energy window to 15%. 132 Although it has been suggested that a medium-energy collimator may be preferred, 129 use of a calibration phantom to derive a conversion coefficient for each camera-collimation system may be a better approach.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…132 Several methods have been explored attempting to overcome this problem when an LEHR is used, including mathematical deconvolution of septal penetration (DSP), 130 image acquisition using 123 I-dual window acquisition (IDW), 133 decreasing the 159-kEV energy window to 15%. 132 Although it has been suggested that a medium-energy collimator may be preferred, 129 use of a calibration phantom to derive a conversion coefficient for each camera-collimation system may be a better approach. 134,135 There have been recent reports on the 123 I-mIBG imaging with solid-state cameras.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…While various methods have been proposed to improve the quantification of 123 I tracers, including a multiple energy window method,9,15 deconvolution of the septal penetration method,17 and a direct empirical conversion method,18 the calibration phantom method has an advantage, which is demonstrated as follows. Although the simplest approach was creating a linear regression equation between measured HMRs with both LE and ME collimators, the empirical method cannot be applicable to other camera-collimator combinations or multicenter study protocols.…”
Section: Discussionmentioning
confidence: 99%
“…This normal cutoff value is concordant with our measurements of a normal H/M ratio on delayed planar imaging for both HSA MIBG and LSA MIBG (2.2 6 0.3 and 2.0 6 0.2, respectively). Verberne et al reported higher H/M ratios in 9 healthy volunteers using a no-carrier-added formulation (20); however, these higher H/M ratios could be attributed to acquisition on medium-energy collimators that reduce septal penetration and scatter of the higherenergy g photons from 123 I (21). As expected, all SPECT H/M ratios were higher than their respective planar values; however, the variability in normal SPECT H/M measurements was high, as previously reported (22).…”
Section: Discussionmentioning
confidence: 99%